The first celebrations of the Mawlid in al-Andalus and Ceuta, according to the Tuhfat al-mugtarib by al-Qastali and the Maqsad al-sarif by al-Badisi - Boloix Gallardo, Bárbara (Anaquel de Estudios Árabes, 2011)
The widespread observation of certain Christian holidays among the Muslim population of al-Andalus inspired the establishment of the Mawlid, the celebration of Mu¬ammad’s birthday, in the Islamic occident during the 13th century. The present article aims to reveal how the Sufi master from Ohanes (Almería) Abý Marw×n al-Yu¬×nis÷, an important spiritual link between al-Andalus and the Magreb, may have introduced this new holiday to both regions, originally in Ceuta and subsequently in al- Andalus. It will also describe what these pioneering celebrations entailed, according to the information extracted from three accounts in the work Tuhfat al-mugtarib (by the Grenadine Ahmad al-Qastali, and one text from the Maqsad al-sarif (by the Magrebi al-Badisi).